Extrapulmonary manifestations of COVID-19: Radiologic and clinical overview - Behzad, Shima; Aghaghazvini, Leila; Radmard, Amir Reza; Gholamrezanezhad, Ali (Clinical imaging, 2020)
COVID-19 is principally a respiratory illness and pulmonary manifestations constitute main presentations of the disease. According to the reported studies, SARS-CoV-2 infection is not limited to the respiratory system and other organs can be also affected. Renal dysfunction, gastrointestinal complications, liver dysfunction, cardiac manifestations, mediastinal findings, neurological abnormalities, and hematological manifestations are among the reported extrapulmonary features. Considering the broad spectrum of clinical manifestations and the increasing worldwide burden of the disease, there is an urgent need to rapidly scale up the diagnostic capacity to detect COVID-19 and its complications. This paper focuses on the most common extrapulmonary manifestations in patients with COVID-19 pneumonia. Further studies are needed to elaborate and confirm the causative relationship between SARS-CoV-2 and the reported extrapulmonary manifestations of COVID-19. •SARS-CoV-2 infection is not limited to the respiratory system and other organs can be affected.•Renal, gastrointestinal, liver, cardiac, neurological, and hematological complications are among the reported extrapulmonary features.•Further studies are needed to elaborate the causative relationship between SARS-CoV-2 and the reported extrapulmonary manifestations of COVID-19.